Oral paracetamol (acetaminophen) for cancer pain - Wiffen, Philip J (Cochrane Database Syst Rev, 2017)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the efficacy of oral paracetamol (acetaminophen) for cancer pain in adults and children, and the adverse events associated with its use in clinical trials.